Trade diversification in Colombia, 1991-2011 (2017)
In this paper we describe the evolution of international trade and the behaviour of export diversification in Colombia during the 1991-2011 period. In order to measure trade diversification and follow its behaviour throughout the period, we employ alternative ways of decomposing trade flows in their intensive and extensive margins, using the latter as a measure of diversification. The results indicate that trade diversification in Colombia is relatively limited, and seems to follow a pattern according to which exports are diversified mainly through increases in the number of products rather than in the number of partners. At the same time imports tend to diversify mainly by increases in the number of countries of origin rather than by the number of products. Furthermore, trade with upper middle-income countries seems to be an important driver of trade diversification.